Maternal use of cough medications during early pregnancy and selected birth defects: a US multisite, case–control study - Martha M Werler; Paul Romitti; Yanyan Cao; Anthony Rhoads; Trudy Burns; Ryan M Carnahan; Kristin M Conway; Allen Mitchell (BMJ Open)
Objective To examine associations between maternal use of cough medications containing dextromethorphan (DM) without guaifenesin (glyceryl guaiacolate (GG)) (‘DM alone’), GG without DM (‘GG alone’) or DM +GG and major birth defects in offspring.Design Population-based case–control study.Setting The multisite, US National Birth Defects Prevention Study.Participants Mothers of 1644 children with neural tube defects (NTDs), 15 110 with non-NTDs, and 10 671 control children without a birth defect diagnosis.Main outcome measures ORs and 95% CIs.Results For NTD analysis, 1.7% of mothers of case children and 1.2% of mothers of control children reported using DM alone, 1.1% and 0.6% GG alone, and 0.4% and 0.2% DM +GG. Respective percentages for non-NTD analysis were 2.2% and 1.9% for DM alone, 1.7% and 1.6% for GG alone, and 0.5% and 0.4% for DM +GG. For all NTDs and subtypes, adjusted OR estimates for DM alone were near the null with 95% CIs that included 1.0. Estimates (95% CI) were 1.8 (1.0 to 3.3) for GG alone and 1.8 (0.6 to 4.8) for DM +GG with all NTDs and 2.2 (1.1 to 4.3) for GG alone with spina bifida. Of the 45 adjusted OR estimates for non-NTDs, 39 ranged from 0.5 to 1.6 with 95% CIs that included 1.0. Near twofold or higher estimates (95% CI) were observed for the remainder and included 1.9 (1.0 to 3.7) for hydrocephalus, 2.9 (1.3 to 6.5) for atrioventricular septal defect and 1.8 (1.1 to 3.0) for transverse limb deficiency with DM alone; 2.1 (1.1 to 4.0) for small intestinal atresia/stenosis and 2.1 (0.9 to 4.5) for omphalocele with GG alone; and 3.2 (1.5 to 6.9) for gastroschisis with DM +GG.Conclusions Maternal use of medications containing DM alone, GG alone or DM +GG showed positive associations with a small number of birth defects. These observations, which should be interpreted with caution due to small proportions of exposed mothers, may represent true signals or chance findings and warrant evaluation in future studies.